Preservasi Pengetahuan Mantra Pengobatan sebagai Tradisi di Kabupaten Pesisir Selatan - Fitri, Helma Fiana; Nelisa, Malta (Lembaga Yasin AlSys, 2024)
This research aims to describe efforts to preserve knowledge of healing mantras as a tradition in Kabupaten Pesisir Selatan. The type of research used is qualitative research with a case study approach. The method used is a descriptive research method. Data collection techniques through interviews and documentation. Research data was obtained from interviews with owners of knowledge about healing spells. Test the validity of the data using source triangulation techniques. The research results can be concluded as follows. First, the selection process begins by selecting where knowledge about healing spells in Kabupaten Pesisir Selatan will be extracted and what type of knowledge about healing spells will be preserved. It was found that three informants still had a lot of knowledge about healing spells in Kabupaten Pesisir Selatan. From the three informants, they obtained 25 knowledge of healing spells and after selection they obtained 19 types of healing spells in Kabupaten Pesisir Selatan. Second, the storage process of storing knowledge of healing spells in Kabupaten Pesisir Selatan will be stored in book form. The knowledge of treatment spells that have been selected will later be recorded, which is useful for maintaining this knowledge so that it does not just disappear. Third, actualization is the final process of preserving knowledge of healing spells in Kabupaten Pesisir Selatan, where after this knowledge is recorded, the book will be given back to the owner of the knowledge so that it can be used for the process of transferring knowledge regarding healing spells in Kabupaten Pesisir Selatan.